Дипольная модель магнитного поля трехфазной электрической цепи - Розов, В.Ю.; Пелевин, Д.Е. (Технічна електродинаміка, 2012)
The principles of construction of dipole mathematical model of external magnetic-field of three-phase electric circuit are considered. To determine the parameters of this dipole model the method based on the equation of power is suggested. The necessity for using three-contour model of three-phase electric circuit model of limited length in general case is grounded. The synthesis of a simplified two-contour model is performed in case of the symmetry of supply voltages.